Alcohol‐tolerant mutants of cyanobacterium Synechococcus elongatus PCC 7942 obtained by single‐cell mutant screening system. Issue 8 (18th May 2017) - Arai, Sayuri; Hayashihara, Kayoko; Kanamoto, Yuki; Shimizu, Kazunori; Hirokawa, Yasutaka; Hanai, Taizo; Murakami, Akio; Honda, Hiroyuki
ABSTRACT: Enhancement of alcohol tolerance in microorganisms is an important strategy for improving bioalcohol productivity. Although cyanobacteria can be used as a promising biocatalyst to produce various alcohols directly from CO2, low productivity, and low tolerance against alcohols are the main issues to be resolved. Nevertheless, to date, a mutant with increasing alcohol tolerance has rarely been reported. In this study, we attempted to select isopropanol (IPA)‐tolerant mutants of Synechococcus elongatus PCC 7942 using UV‐C‐induced random mutagenesis, followed by enrichment of the tolerant candidates in medium containing 10 g/L IPA and screening of the cells with a high growth rate in the single cell culture system in liquid medium containing 10 g/L IPA. We successfully acquired the most tolerant strain, SY1043, which maintains the ability to grow in medium containing 30 g/L IPA. The photosynthetic oxygen‐evolving activities of SY1043 were almost same in cells after 72 h incubation under light with or without 10 g/L IPA, while the activity of the wild‐type was remarkably decreased after the incubation with IPA. SY1043 also showed higher tolerance to ethanol, 1‐butanol, isobutanol, and 1‐pentanol than the wild type. These results suggest that SY1043 would be a promising candidate to improve alcohol production using cyanobacteria. Biotechnol. Bioeng. 2017;114: 1771–1778. © 2017 Wiley Periodicals, Inc. Abstract : An isopropanol (IPA)‐tolerant mutant strain of cyanobacterium Synechococcus elongatus PCC 7942 (maximum growth allowance concentration of 30 g/L) was acquired by using UV‐C induced random mutagenesis and a single cell liquid culture system. The tolerant strain, SY1043, has a higher tolerance to some other alcohols including ethanol (30 g/L), 1‐butanol (12 g/L), isobutanol (20 g/L), and 1‐pentanol (6 g/L). SY1043 can be useful biocatalyst for improving alcohol production.